Sphaeronycteris toxophyllum - Rubi Angulo, S. (2008)
Sphaeronycteris toxophyllumPeters, 1882, is a rare bat known as the visored bat because it has a unique outgrowth on the face. This typical hornlike growth is sexually dimorphic, larger on males than on females, and also better developed in adults than in juveniles. This bat is endemic to tropical South America and present in Venezuela, Peru, Colombia, Bolivia, Brazil, and Ecuador. It is present from the Amazon Basin to mountainous regions up to 3,000 m in elevation and has been captured in secondary rain forest, cloud forest, deciduous forest, and open areas. The International Union for Conservation of Nature and Natural Resources conservation status is Lower Risk/Least Concern.